Jamaica : Tenth Review Under the Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jamaica's Tenth Review Under the Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria (PCs). Macroeconomic stability continues to strengthen. Inflation and the current account deficit have fallen to historical lows, a product of the low oil prices as well as the ongoing economic adjustment. The program remains on track. All PCs for end-September 2015 and structural benchmarks for the review period were met. Based on the authorities' continued strong program implementation and their forward-looking policy commitments, the IMF staff recommends completion of the tenth review.